Karakteristik Mekanik Komposit Polyester E-Glass dengan Stacking Sequences [0°, 90°, 0°] - Ilhamdi Ilhamdi; Dony Hidayat; Fadli Febriyan (Department of Mechanical Engineering, Universitas Andalas, 2020)
There is one fact that lead composite material to be a unique material among others. Its properties could be settable or flexible with arrangement of composition, orientation and production procedure. Meanwhile other materials seemed to have fixed set after fabrication. Nowadays, one of the widely developed structural composite is polymer based composite with inorganic reinforcement. It is useful in automotive or aircraft component because reasonable strength and much lower density compare to metal. In this study, e-glass fibers were manually laminated with polyester resin in open die using brush. This method is widely known as hand lay up. Fibers were set in stacking sequences of 0o, 90o, and 0o, means a fiber is in perpendicular direction to its neighbor fibers. After complete dried up, composite panel is cut of accordingly to ASTM standard for tensile and compressive testing specimen. In order to examine hole effect, center of gage length specimen was drilled off. Namely, specimen will be distinguished as no hole specimen and open hole specimen. Results showed tensile strength of 200.58 MPa and 155.22 MPa, compressive strength of 335.73 MPa and 254.1 MPa, for no hole and open hole specimen respectively. Introducing open hole reduces mechanical strength of composite both tensile and compressive. It could be mechanical consideration for safety design of material composite application. Failure mechanism of composite is also influenced by existence of open hole. When no hole specimen will experience failure at near to grip (LAT), open hole specimen has fracture line propagate from hole into width (LGM).